Cry-baby [videorecording (DVD)] - Talalay, Rachel, 1958-; Waters, John, 1946-; Depp, Johnny; Locane, Amy, 1971-; Tyrrell, Susan, 1945-2012; Pop, Iggy, 1947-; Lake, Ricki; Lords, Traci; Mailer, Stephen, 1966-; Burrows, Darren E., 1966-; McGuire, Kim D.; Bergen, Polly, 1930-2014; et al. (Universal Studios Home Entertainment, 2005)
A spoof and homage to 1950's teen rock melodramas. Cry Baby is a rebel with a gang of rough friends. Allison is the straight-laced girl who falls for him.